A systematic review of tropical cyclone disaster management research using remote sensing and spatial analysis. (1st September 2017) - Hoque, Muhammad Al-Amin; Phinn, Stuart; Roelfsema, Chris
Abstract: Tropical cyclones are among the most dangerous and devastating natural disasters affecting life, property and environment. The use of remote sensing and spatial analysis has significantly increased to manage the on-ground impacts of these disasters with rapid advances in a wide range of data availability and processing techniques. This paper reviews recent studies of on-ground cyclone disaster management using remote sensing and spatial analysis in the context of response, recovery, prevention/reduction and preparedness to find out the key knowledge gaps for future research. The study used a systematic quantitative literature review technique to assess the past 21 years of research. Following the systematic search and developed selection criteria, the relevant original published articles on cyclone disaster management using remote sensing and spatial analysis were selected. The selected literature was then categorised and analysed based on the particular research focus. Our findings showed that most of the studies were concentrated in Asia (55%) and North and Central America (40%). The extensive use of remote sensing and spatial analysis started after 2004 and largely focused on the preparedness (34%) and prevention/reduction (32%) phases. Nearly all studies used the optical imagery, and the use of SAR imagery was limited. The object-based classification approach was rarely used under post-classification comparison techniques for overall tropical cyclone impact assessment and recovery. Very limited studies examined tropical cyclone risk assessment incorporating mitigation capacity and spatial multi-criteria using the analytical hierarchy process (AHP). A simple modelling approach is required for producing detailed cyclone risk models. Most of the studies were conducted at the regional scale without validation of results. Cyclone risk mapping and modelling should consider future climate changes scenarios at the local scale. Future research is needed to cover reported knowledge gaps for improving cyclone disaster management. Highlights: Cyclone disaster management research using geospatial techniques are critically reviewed. The relevant literature were selected using systematic search and developed criteria. Most of studies were concentrated in Asia (55%) and North and Central America (40%). Nearly all studies used the optical imagery, and the use of SAR imagery was limited. A simple validated cyclone risk modelling approach is required at local scale integrating climate change scenarios.